PENGARUH BRAND IMAGE DAN SERTIFIKASI HALAL TERHADAP MINAT BELI PELANGGAN (STUDI KASUS SUPERKUE BOGOR) (STAI BHAKTI PERSADA BANDUNG, 2018)
Brand image is the name, term, sign, symbol, design that is intended to identify goods or services offered by the company as well as product differentiation. As a Muslim-majority society, it should care about the process of making halal food, to avoid things that are forbidden in Islam by paying attention to halal certification. Because a product that has a halal certificate, the halal is guaranteed. The purpose of this study was to determine the extent of the influence of brand image and halal certification on customer buying interest. The method used is multiple linear regression analysis, based on the results of multiple linear regression analysis found that brand image and halal certification jointly influence customer buying interest. This can be known by the F count value of 10.746 with a significance level of 0.000 greater than 0.05, which means that statistically prove that brand image and halal certification have a positive effect on customer buying interest